Sustainable Impact of Zakat, Infaq, and Sadaqah on Multidimensional Poverty and Enhancing Economic Growth in 34 Indonesia Provinces - Suci Wulandari Siregar; Jasman, Zahra Ramadani; Indarningsih, Nur Aisyah; Hasbi (Universitas Muhammadiyah Yogyakarta, 2025)
This research delves into the crucial role of Zakat, Infaq, and Sadaqah (ZIS) in alleviating multidimensional poverty and enhancing economic growth across Java's provinces in Indonesia during the period from 2013 to 2022. Utilizing the Panel Vector Error Correction Model (PVECM), the study explores the causal relationships between ZIS and key socio-economic indicators, including Gross Regional Domestic Product (GRDP), multidimensional poverty indices, and overall economic growth. The results indicate that ZIS significantly reduces poverty, as evidenced by its negative impact on the percentage of the poor population (P0), the poverty depth index (P1), and the poverty severity index (P2). In addition to its effectiveness in poverty alleviation, ZIS also exerts a positive and significant influence on economic growth, highlighting its dual role as both a redistributive mechanism and an economic catalyst. These findings suggest that, when effectively managed, ZIS can play a vital role in addressing both immediate social needs and long-term economic development goals. The study underscores the importance of optimizing ZIS management to maximize its impact on poverty reduction and economic sustainability. Moreover, the research suggests that targeted and productive use of ZIS can lead to more inclusive economic growth, benefitting a broader segment of society. This study contributes to the growing body of literature on the economic and social impacts of ZIS, providing empirical evidence of its potential to drive meaningful change in Indonesia's socio-economic landscape.